Associations of loneliness with mental health and with social and physical activity among university students in Germany: results of the COVID-19 German student well-being study (C19 GSWS) - Wenig, Vanessa; Heumann, Eileen; Stock, Christiane; Busse, Heide; Negash, Sarah; Pischke, Claudia R.; Heinrichs, Katherina (Frontiers in Public Health, 2023)
University students are at high risk for loneliness with a potential negative impact on health. The COVID-19 measures disrupted students' academic routine and social life, which might have affected their perception of loneliness. This study investigated the prevalence of perceived loneliness among university students in Germany during the COVID-19 pandemic and its associations with mental health, behavioural outcomes, and sociodemographic characteristics.The COVID-19 German Student Well-being Study (C19 GSWS) collected data from five German universities from October 27th to November 14th, 2021, resulting in a sample of 7,203 respondents. Associations of loneliness with depressive symptoms, anxiety, social and physical activity, as well as sociodemographic characteristics, were analysed using multivariable logistic regressions.Results: A total of 20.6 % of students reported loneliness. Students with depressive or anxiety symptoms had more than eight-or sixfold odds, respectively, for reporting loneliness (depressive symptoms: